Jogos de empresas : um estudo da utilização em cursos de graduação em Administração no Estado de São Paulo - Neves, Joziel Pereira (2007)
On the basis of the existing contradiction enters the effectiveness of the business games, and its low use in courses of graduation in administration, evidenced in studies of diverse researchers, searched to investigate the conditions of use of the business games in the formation of administrators, in the management schools of the state of São Paulo. Through one it searches survey, of descriptive nature, that used a questionnaire auto-managed, formulated from studies related to the use of business games and pedagogical and aspects technician, got 130 answers in a population of 347 searched courses of administration. In not using institutions of games of companies, one investigated the reasons for not the use of games, the perceptions concerning factors favorable and favorable to the practical one of games, as well as the intention to use. In the courses that use games of companies, the inquiry was proceeded with emphasis in identifying to aspects technician and pedagogical employees, the satisfaction how much to the gotten results and aspects favouries and difficulties to the use of games. As results of the research, it was proven that: 48% of the management schools of the state of São Paulo regularly use games of companies in its courses of graduation in administration; of the 130 management schools respondent, only 2 do not intend to use; 95% of the management schools that they use the tool are satisfied with the results; it has predominance for the games general or total enterprise, with competition between the participants and organized in teams; preference for games developed internally and acquired of specialized companies, both with 29% of the preference, being that the number of IES satisfied with bought games is 4,5 times bigger that the number of satisfied management schools with games developed internally; it has, in general way, agreement of the respondents in relation to the benefits generated for the tool pointed by literature, being distinguished with more than 90%, the importance in the professional formation I stimulate, it to the functional thought, the contribution to the cognition learning I stimulate and it to the work in team; As aspects difficulties to the practical one of games, lack of trained professors and costs of acquisition had been distinguished it. The main conclusions that if arrived with this study, are of that the use of games of companies in the formation of managers, will grow significantly in such a way in the short one how much in the average stated period, as well as the identification of a chance of teaching professional performance and technique, in the measure that relative the economic limitations to the acquisition costs and implantation of games, will have to be surpassed by the efforts of professionals specialized in the development and the dynamics of games, as well as for the management schools interested in its use.